Software and methodological support for additional professional courses: ideas, problems, monitoring - O. D. Prokhorenko; S. V. Morin; O. A. Kozyreva (Вестник Северо-Кавказского федерального университета)
Introduction. The article identifies the possibilities of modeling and using software and methodological support for additional professional courses. Definitions directly related to the process and products of theorization of software and methodological support for additional professional courses have been clarified. The purpose of the work is to define the idea of research and clarification, theorization and modeling of software and methodological support for additional professional courses. Materials and methods. The methods of studying and describing the selected area of scientific research and scientific research are defined as pedagogical and professional modeling, scientific theorizing, technologization of pedagogical processes and analysis of the quality of the identified pedagogical phenomena and refined scientific and pedagogical prospects. Results and discussion. Ideas for theorizing and modeling software and methodological support for additional professional courses are defined in classical and innovative search, solving problems and issues of lifelong education. The integrity and uniqueness of the highlighted ideas for software and methodological support for additional professional courses reflect the modern ideology of the development and use of software and methodological support for additional professional courses. The universality of the ideas of theorization and technologization of pedagogical processes makes it possible to identify and justify in a timely manner the problems of modeling and using software and methodological support for additional professional courses as a system of meanings and contradictions that guarantee the solution and optimization of the components of the holistic development of both the individual and the environment; models of software and methodological support for additional professional courses as idealized resources that facilitate the objectification of needs in solving all didactic and scientific-pedagogical problems (illustration, study, clarification, addition, modification, etc.); principles of creation and implementation of software and methodological support for additional professional courses as a system of values and meanings of theorization and technologization of the described pedagogical process and pedagogical phenomenon; pedagogical conditions for improving the quality of modeling and using software and methodological support for additional professional courses as case models that variably determine and implement level-level opportunities for personal development and the theorized pedagogical process. Conclusion. By building prospects for theorizing and implementing ideas for improving the quality of modeling and using software and methodological support for further education courses, we can distinguish in the integrative representation of the direction and prospects of an individual’s achievements three types of solving professional and pedagogical problems theorized in the work (algorithmic, creative-stimulative and innovative-promising).